Parental Decision Making in Male Circumcision. Issue 2 (March 2015) - Sardi, Lauren; Livingston, Kathy
Abstract Purpose: To study which healthcare professionals (HCPs) firstasked parents about their decision regarding circumcision; whether parents felt they were given enough information by their HCP; and what reasons parents cited for their decision. Study Design and Methods: Bilingual questionnaires were administered to parents and expecting parents of boys (N = 60). Close-ended survey responses were analyzed through factor analysis to ascertain what types of beliefs parents used in their decision making, whether they felt they had enough information, and who first asked them about their decision. Results: Nurses were most likely to be the first HCPs to ask parents about circumcision. Parental personal and cultural beliefs played an equal or more important role in influencing decision making than medical information received. However, some parents noted that there was a lack of access to accurate information regarding risks and benefits of male circumcision. Clinical Nursing Implications: Nurses continue to play a critical role in acquisition of knowledge surrounding male circumcision and serve as important liaisons between parents and the proxy consent process. Nurses, as well as other HCPs, should discuss circumcision early in pregnancy so parents have ample time to ask questions, gather information, and make an appropriate decision.